The Role of Zakat Literacy and Zakat Spirituality on Muzakki Compliance Behavior - Muhammad Yusran; A. Maharani Dozabrina; Nuraeni M; Nur Hidayah; Erty Rospyana Rufaida (Indonesian Journal of Business Analytics, 2024)
This study examines the influence of zakat literacy and zakat spirituality on the compliance behavior of muzakki in paying zakat. The independent variables are zakat literacy and zakat spirituality, while the dependent variable is compliance behavior in paying zakat. A quantitative approach was employed, with the research conducted in Majene District, West Sulawesi. The population consists of muzakki who meet the criteria for the study. A sample of 80 respondents was selected using purposive sampling, with calculations based on the percentage formula. Data analysis was performed using multiple linear regression. The results show that both zakat literacy and zakat spirituality significantly and positively influence the compliance behavior of muzakki in paying zakat.